2016
DOI: 10.1038/hdy.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal genetic survey identifies temporal shifts in the population structure of Dutch house sparrows

Abstract: Dutch house sparrow (Passer domesticus) densities dropped by nearly 50% since the early 1980s, and similar collapses in population sizes have been reported across Europe. Whether, and to what extent, such relatively recent demographic changes are accompanied by concomitant shifts in the genetic population structure of this species needs further investigation. Therefore, we here explore temporal shifts in genetic diversity, genetic structure and effective sizes of seven Dutch house sparrow populations. To allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 99 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Identifying all effective causes of population decline are urgently needed to act and prevent the extinction of this northern cluster. Continued monitoring of sensitive populations would be needed to infer the impact of current demographical trends on genetic diversity and structure through longitudinal studies (Cousseau et al 2016). In conclusion, this study highlighted the complex patterns and drivers of genetic variation in a widely distributed long-distant migrant bird and helped inform the scale of conservation actions required to limit population declines and identify vulnerable populations where targeted effort are required to prevent future extinctions.…”
Section: Discussionmentioning
confidence: 85%
“…Identifying all effective causes of population decline are urgently needed to act and prevent the extinction of this northern cluster. Continued monitoring of sensitive populations would be needed to infer the impact of current demographical trends on genetic diversity and structure through longitudinal studies (Cousseau et al 2016). In conclusion, this study highlighted the complex patterns and drivers of genetic variation in a widely distributed long-distant migrant bird and helped inform the scale of conservation actions required to limit population declines and identify vulnerable populations where targeted effort are required to prevent future extinctions.…”
Section: Discussionmentioning
confidence: 85%
“…Harper et al (2006) showed that the allele frequencies of the Adonis blue butterfly, Polyommatus bellargus (Lycaenidae), populations in the United Kingdom changed from 1896 to 1998-1999 because of genetic drift, local extinction, and recolonization. Cousseau, Husemann, Foppen, Vangestel, and Lens (2016) and Kekkonen et al (2011) also demonstrated that the genetic differentiation of the house sparrow in Europe increased because of a decline in its population size. If all remnant populations of a target species have experienced a severe bottleneck, the genetic information of the populations before human disturbance, in addition to that of extant populations, could be used to construct more accurate and suitable conservation strategies.…”
Section: Introductionmentioning
confidence: 97%